2020
DOI: 10.1108/jsit-01-2020-0010
|View full text |Cite
|
Sign up to set email alerts
|

Effect of gratification on user attitude and continuance use of mobile payment services: a developing country context

Abstract: Purpose This study aims to investigate the gratifications driving the attitude and continuance use of mobile payment services in developing country context, such as Ghana. Also, the moderating effect of income and education on gratifications and attitude of users is explored. Design/methodology/approach Data was collected from conveniently sampled 361 users of mobile payment services in Ghana. A questionnaire, which mainly contains five-point Likert scale questions, was used to collect the data. The study ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 76 publications
4
20
0
Order By: Relevance
“…Regarding in-store technologies, Acuti et al (2020) showed that the type of communication of QR code influences the perceived value of the product: when the message content is hedonic, it generates a greater perceived value of products. Alhassan et al (2020) have also shown that ease of use and usefulness gratifications significantly influence attitudes toward the use of mobile payment services. Roux (2020) has also identified four gratifications related to the use of wayfinding screens in shopping malls (convenient process, interactive process, informational content and entertaining content).…”
Section: Literature Review 21 Phygital and Interactive Technologiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding in-store technologies, Acuti et al (2020) showed that the type of communication of QR code influences the perceived value of the product: when the message content is hedonic, it generates a greater perceived value of products. Alhassan et al (2020) have also shown that ease of use and usefulness gratifications significantly influence attitudes toward the use of mobile payment services. Roux (2020) has also identified four gratifications related to the use of wayfinding screens in shopping malls (convenient process, interactive process, informational content and entertaining content).…”
Section: Literature Review 21 Phygital and Interactive Technologiesmentioning
confidence: 99%
“…Moreover, the UGT approach has been mobilized to explore the adoption factors of online technologies such as chatbots (Rese et al, 2020) and in-store technologies such as QR codes (Acuti et al, 2020) and mobile payment services (Alhassan et al, 2020). The findings of Rese et al (2020) highlighted that utilitarian and hedonic factors have a positive impact on the acceptance of chatbot software programs.…”
Section: Literature Review 21 Phygital and Interactive Technologiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, several past studies on mobile payment continuance (e.g. Alhassan et al, 2020;Shao et al, 2019) only included a few direct antecedents of continuance intention in their research models. Therefore, the research objectives of this study are (1) to determine the antecedents that affect continuance intention to use mobile payment and (2) to develop a multi-dimensional model based on the cognitive-affective-conative (CAC) framework.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, several past studies on mobile payment continuance (e.g. Alhassan et al. , 2020; Shao et al.…”
Section: Introductionmentioning
confidence: 99%